cAMP-induced Mitochondrial Compartment Biogenesis: ROLE OF GLUTATHIONE REDOX STATE - Yoboue, Edgar D. (American Society for Biochemistry and Molecular Biology, 2012)
Cell fate and proliferation are tightly linked to the regulation of the mitochondrial energy metabolism. Hence, mitochondrial biogenesis regulation, a complex process that requires a tight coordination in the expression of the nuclear and mitochondrial genomes, has a major impact on cell fate and is of high importance. Here, we studied the molecular mechanisms involved in the regulation of mitochondrial biogenesis through a nutrient-sensing pathway, the Ras-cAMP pathway. Activation of this pathway induces a decrease in the cellular phosphate potential that alleviates the redox pressure on the mitochondrial respiratory chain. One of the cellular consequences of this modulation of cellular phosphate potential is an increase in the cellular glutathione redox state. The redox state of the glutathione disulfide-glutathione couple is a well known important indicator of the cellular redox environment, which is itself tightly linked to mitochondrial activity, mitochondria being the main cellular producer of reactive oxygen species. The master regulator of mitochondrial biogenesis in yeast (i.e. the transcriptional co-activator Hap4p) is positively regulated by the cellular glutathione redox state. Using a strain that is unable to modulate its glutathione redox state (Δglr1), we pinpoint a positive feedback loop between this redox state and the control of mitochondrial biogenesis. This is the first time that control of mitochondrial biogenesis through glutathione redox state has been shown.